(aS)-Glucosciadopitysin, a New Biflavonoid Glycoside from the Leaves of Ginkgo biloba and Osteogenic Activity of Bioflavonoids - Se Yun Jeong; Kwang Ho Lee; Seon Hee Kim; Min Hye Yang; Gakyung Lee; Ki Hyun Kim (Plants)
The leaves of Ginkgo biloba have been used in treating freckles and effectively reducing cough and sputum in folk medicines. Recently, investigations into the correlation between ginkgo leaves and the proliferative activity of osteogenic differentiation have been conducted. However, bioactive compounds that enhance osteogenesis or exhibit osteoporosis prevention from G. biloba have not been fully identified. Phytochemical investigation of the MeOH extract of G. biloba leaves led to the isolation and identification of a new biflavonoid glycoside, (aS)-glucosciadopitysin (1), along with five flavonoids (2–6), through LC/MS-guided isolation approach. The structure of the new compound 1 was elucidated by the spectroscopic methods, including 1D and 2D NMR analysis, as well as HR-ESIMS. The absolute configuration of sugar moiety was established through acid hydrolysis, followed by chemical derivatization reaction and the axial chirality arising from the biaryl system with substituents was determined by electronic circular dichroism (ECD) calculations. The isolated flavonoids (1–6) were tested for their effects on mesenchymal stem cell (MSC) differentiation at 20 μM using Oil Red O and alkaline phosphatase (ALP) staining. Ginkgetin (2) was further evaluated for osteogenic activity on C3H10T1/2 cells at concentrations of 1, 2.5, 5, and 10 μM for 10 days. ALP staining and RT-PCR assessed the gene expression of osteogenic markers ALP and osteopontin (OPN). Ginkgetin (2) demonstrated the strongest osteogenic activity, significantly increasing the expression of ALP (12.5-fold) and OPN (4.0-fold) at 10 μM, comparable to the positive control, oryzativol A. Ginkgetin (2) shows potential as a therapeutic agent for osteopenia by promoting osteogenesis in MSCs, suggesting its promising role in treating osteoporosis.